Physiological characterization and bioactive compounds of promising accessions of cowpea (Vigna unguiculata L. Walp) in the Peruvian Amazon - Murga-Orrillo, Hipolito; Chuquímez Gonzales, Jhon K.; Arévalo López, Luis A. (Frontiers in Agronomy, 2024)
Cowpea production in the Peruvian Amazon is increasing due to its ability to adapt to diverse environments, its contribution to soil conservation, and its versatility of uses. This crop is particularly valuable in human nutrition due to its high nutritional quality and nutraceutical properties of its bioactive compounds. The aimed was to evaluate physiological aspects of the plant and bioactive compounds of the grain of the cowpea accessions PER1005854, PER1005851, and PER12645, and to analyse how rice husk mulch, screw tree litter, and oil palm fibre influence the physiology of these accessions. The experiment was conducted from November 2022 to March 2023, in Yurimaguas, Loreto, Peru. The application of organic mulches demonstrates a significantly positive impact on the growth of cowpea accessions during their vegetative phase. This effect is possibly attributed to increased water availability, as the mulch reduces soil evaporation. In particular, cowpea accessions PER12645 and PER1005851 exhibit desirable physiological characteristics for grain production, with short cycles of 71 days and higher yields of 1141 and 1125 kg/ha respectively. In contrast, accession PER1005854 is distinguished by its higher biomass production, reaching a value of 14497 kg/ha, a relevant trait for foliage production and its contribution to soil conservation. The grains of accession PER12645 exhibit superior antioxidant activity of 26.3 μmolTG/g, which is associated with the black color of its seed coat.